Analisis Kredit Macet Pada Produk Pembiayaan Murabahah di PT. BPRS Sarana Prima Mandiri Pamekasan - Nurul Hidayati; Faiqotul Jannah; Moh. Helmi Hidayat (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
One of the determinants of success in a banking company is good and optimal management of financial resources and precisely choosing partners for cooperation with existing capital turnover. This study aims to find out how the process of settlement of bad loans in murabahah financing at PT.BPRS SPM Pamekasan. The method used is descriptive qualitative method. The resulting data is in the form of qualitative data, which was developed using a descriptive method. Descriptive method is a type of research that provides an overview or description of a situation as clearly as possible without any treatment of the object under study. Documentation in this journal research uses literature books and financial reports of PT. BPRS SPM in 2015- 2021, where in the data we carry out data observations, analyzes and draw conclusions. The research results show that the number of murabaha financing customers from 2015-2021 has increased. Whereas murabahah financing customers who are smooth and non-performing in 2015-2021 have more bad loans (bad credit), because one of them is caused by the large number of businesses that have gone bankrupt and the income that is not smooth in running their business. So it is advisable for bank management to always analyze the development of a customer's business to ensure partner customers do not commit bad loans to the bank.